PELATIHAN PENGELOLAAN KEUANGAN USAHA HIDROPONIK SEBAGAI SOLUSI PETANI PERKOTAAN URBAN FARMING POSYANTEK KECAMATAN SETU, KOTA TANGERANG SELATAN - Supatmin Supatmin; Sutiman Sutiman; Krisnaldy Krisnaldy; Hengki Hermawan; Akhmad Akbar (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
Devotion to the community was an integral part of tri dharma higher education institutes which in its implementation cannot be separated from two dharma a dream and the other , as well as involving he utterly destroyed all the sivitas its products: he got from his lecturers , what the students are , of teaching staff as well as alumni .Through pkm academic sivitas can attend in tengah- heart of communities .See the campus that does away with the location Posyantek Setu , Tangerang Selatan, and so are mandatory for pamulang university (Unpam) to participate in help various problems that are faced by the good close or far away. The science of financial growth management especially financial management about the way find out about the management of the funds systematically, so that financial management is not only mastery of a collection of knowledge but also by is the process of discovery. What problems arose that is they did not the media that is adequate to explain a concept, Learning that effective. But most schools is still feeling a lack of facilities and infrastructures are. There are still quite information is. This will make it tougher for masyrakat in understanding the concept of, so to be an instructor should look to be creative and innovative. The result of the activities of its service is the citizen as well as the caretaker posyantek financial management that the problem is very important and is far from expected. The caretaker posyantek also find as much financial problems must be improved especially about how to get funds and also the most difficult too how to use the funds that there could be used effectively and efficiently. The obstacles faced on both posyantek managers and residents are unable to exploit existing conditions to use the funds available and have no further a partner of funding to run a business which is run wheels. The result of devotion and activities are the residents of the financial management problems posyantek aware very important far than expected. Posyantek also realized the many financial problems must be solved about receive fund and also most difficult is also the manner of use funds can be used in business hydroponic and will become a pioneer in the area, the held with a base to this training. And obstacles faced on both the posyantek and residents will use is no existing conditions to use funds and support of the government touching optimally.Hydroponic if managed well should will make a substitute for farmers in pertotaan so will the need for vegetables awarded.Keywords: Training, hydroponic and urban farmin